PTEN gene silencing contributes to airway remodeling and induces airway smooth muscle cell proliferation in mice with allergic asthma - Wen, Xin; Yan, Jing; Han, Xin-Rui; Zheng, Gui-Hong; Tang, Ran; Liu, Li-Fang; Wu, Dong-Mei; Lu, Jun; Zheng, Yuan-Lin (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: Allergic asthma is a complex genetic disorder that involves interactions between genetic and environmental factors. Usage of PTEN may be a good therapeutic strategy for the management of allergic inflammation. Thus, the present study aims to explore the effects of phosphatase and tensin homolog (PTEN) gene silencing on airway remodeling and proliferation of airway smooth muscle cells (ASMCs) in a mouse model of allergic asthma. Methods: A total of 56 healthy female BABL/c mice (weighing between 16 to 22 grams) were selected and were assigned on random into ovalbumin (OVA; mice were stimulated with OVA to induce allergic asthma), OVA + si-PTEN, normal saline (NS; mice were treated with normal saline) and NS + si-PTEN groups. Masson staining was employed in order to observe lung tissue sections. Immunohistochemical staining was used to detect the expression of α-SMA+. Gene silencing was conducted in the NS + si-PTEN and OVA + si-PTEN groups. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blotting were used to detect the mRNA and protein expressions of PTEN in ASMCs of each group. CCK-8 assay and flow cytometry were performed to determine the cell proliferation rate and cell cycle. Results: Airway remodeling and changes of smooth muscle layer were found in allergic asthmatic mice with thick airway walls. The expression of alpha smooth muscle actin (α-SMA+) was significantly higher in ASMCs of the OVA, OVA + si-PTEN and NS + si-PTEN groups compared with ASMCs of the NS group. The mRNA and protein expressions of PTEN reduced in the OVA, OVA + si-PTEN and NS + si- PTEN groups. The rate of ASMCs proliferation in OVA, OVA + si-PTEN and NS + si-PTEN groups were significantly higher than the NS group. The proportion of ASMCs in S and G2 stages increased, while the number of cells in the G1 stage decreased after PTEN gene silencing. Conclusions: These results demonstrated that PTEN gene silencing might promote proliferation of ASMCs and airway remodeling in a mouse model of allergic asthma.